Terapi Aktivitas Kelompok dengan Terapi Butterfly Hug Terhadap Tingkat Kecemasan Lansia di Panti Werdha Kasih Ayah Bunda - Ameliani, Indri; Siti Robeatul Adawiyah; Adilah Salsabila; Ahmad Kurtusi; Aninda Rizki Maulida; Anis Nurfaidah; Anisa; Dida Ningtias; Dita Faradillah; Dwi Sinta (Yayasan Inspirasi El Burhani, 2025)
Introduction: The elderly are individuals who have entered the age of 60 years and above. The World Health Organization (WHO) classifies the elderly in several categories: middle age (45-59 years), elderly (60-74 years), elderly (75-90 years), and very old age (90 years). As they age, the elderly are more prone to experiencing anxiety disorders that can impact their quality of life. Objective: The purpose of Butterfly Hug Group Activity Therapy is to reduce anxiety in the elderly. Method: This group activity therapy has 3 stages, namely the orientation stage, the work stage with the administration of butterfly hug therapy, and the termination stage. Result: The population in this activity was the elderly totaling 13 people by distributing the